1988
DOI: 10.1017/s0950268800029265
|View full text |Cite
|
Sign up to set email alerts
|

Species identification, antibiotic sensitivity and slime production of coagulase-negative staphylococci isolated from clinical specimens

Abstract: SUMMARYTwo hundred and seventy-five consecutive clinical isolates of coagulasenegative staphylococci, including strains associated with disease, contaminants and skin colonizers, were speciated, tested for slime production and for their sensitivity to a range of antibiotics. Staphylococcus epidermidis was the most commonly identified species, comprising 63 % of all isolates. Slime production was detected in half the strains of Staph. epidermidis, Staph. haemolyticus and Staph. saprophyticus but was rare in oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…This study showed that S. epidermidis was the most common CoNS species comprising 43% of all isolates similar to that of other reports [11][12][13][14][15][16] . CoNS was reported as an important cause of blood stream infections and the second most common source after wound swabs in a hospital in Lebanon and Kuwait [17][18] .…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that S. epidermidis was the most common CoNS species comprising 43% of all isolates similar to that of other reports [11][12][13][14][15][16] . CoNS was reported as an important cause of blood stream infections and the second most common source after wound swabs in a hospital in Lebanon and Kuwait [17][18] .…”
Section: Discussionsupporting
confidence: 91%
“…Tube method is a qualitative method for the detection of biofilm production as it was difficult to differentiate between moderate and weak biofilm producers [15]. The results were correlated with previous studies [12,13].…”
Section: Discussionsupporting
confidence: 83%
“…In terms of biofilm presence or absence, 18 (28.12%) isolates were non-biofilm producers while 46 (71.87%) isolates were positive for biofilm production. The results demonstrated that tube method is easy to perform while interpretation of the results is quite complicated particularly with the novice observer, so it cannot be recommended as general screening test for determination of biofilm production [16,15]. In addition, micro-plate assay showed that 56.25% of the isolates were positive for biofilm production.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen patients (73%) were colonized by several different S. haemolyticus strains which were isolated from all body sites predominantly from the groin. A lower prevalence of S. haemolyticus has been reported in some studies (West et al 1986;Eisenberg et al 1987) however Deighton et al (1988) found it to be a common skin colonizer.…”
Section: Disctusstonmentioning
confidence: 80%